REALITIES in health disparities: Researching Evidence-based Alternatives in Living, Imaginative, Traumatised, Integrated, Embodied Systems - de Andrade, Marisa; , and The REALITIES Consortium (Frontiers in Public Health, 2024)
Introduction Under the backdrop of pervasive health inequalities, public health professionals, researchers and non-academic partners in the United Kingdom are mobilising to understand how and in what ways community assets can address health disparities at scale in complex systems. While there is recognition that cultural, natural and community resources can improve health outcomes, these are unequally dispersed with lack of integration in communities and health and social care systems. Researching Evidence-based Alternatives in Living, Imaginative, Traumatised, Integrated, Embodied Systems (REALITIES) is a participatory action research Scottish consortium of 57 with established community asset hubs in five localities with strong relationships uniting conflicting ways of seeing the world. Our collective of lived and felt experience community members, community-embedded researchers, academics and non-academics draws upon a variety of practices, methods, datasets and philosophies to expand existing approaches to tackling health inequalities. Methods We present conceptual and theoretical underpinnings for our co-produced systems-level model and empirical findings from testing REALITIES across three disadvantaged localities (November 2022, ongoing). After explaining the context that led to the development of the new scalable REALITIES model for integrated public systems to interface with ‘assets’, we detail philosophical pillars and guiding principles for our model and how we applied these mechanisms to explain how integrated partnership working can lead to improved health outcomes across multiple public systems. Results We present a meta-analysis from co-producing and testing the model, showing how measuring change in complex public systems involves critical investigation of People, Process, Place, Price, Power and Purpose. Our critique reflects on power imbalances and inequities in Research-practice-Policy (RPP) partnerships and suggestions for how to nurture healthy ecosystems: overcoming barriers and enabling participation; reflecting on challenges of scaling up, testability and complexity of RPP partnerships; moving from siloed learning to transdisciplinary collaboration in practice; ensuring knowledge exchange has direct impact on communities and frontline practitioners; embedding relational ethics and safeguarding into daily practice. Discussion We propose the REALITIES model to unite alternative, sometimes conflicting, ways of thinking about public systems and community assets by continuously reflecting on entanglements between different assumptions about knowledge, reality, evidence, and unnecessary binaries between creative methodologies and scientific method.